Furniture inventory control: using material requirement planning - Mohd Nor, Norasmiha; Ng, Ying Hui; Sazali, Aiman Syakirin; Lee, Xin Tian; Halimirizal, Muhammad Saiful Hasif; O, Jin Yee; Cheam, Kai Wen (Penerbit UTHM, 2020)
Production planning and control (PPC) system is essential to a manufacturing unit of a company to ensure efficient, effective, and economical operation. The finalization of production process is control by the adaption of product design it is based on the production and subsequent production plan. PPC could help company in finding out the problems of resources utilization, low productivity, and inventory management (Juneja, 2020). Production controls and guarantees that the production team to reap the target of the production, with most appropriate usage of resource or assets, managing the quality, and save costs.